The Impact of ChatGPT Formative Feedback on EFL Learner - Hidayat, Mas Zia Ahdaan Ta'ajuddin; Pariyanto, Pariyanto (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2024)
This study uses quantitative research design, and aims to analyze the impact of ChatGPT formative feedback in improving the quality of EFL learners’ narrative essay writing. The 16 participants are English Literature students of Universitas 17 Agustus 1945 Surabaya. In rating the pre-feedback and post-feedback narrative essays, the researcher serves as the first rater, accompanied by another rater, as well as ChatGPT automated feedback as means of comparison. In rating the essays, a narrative essay rubric from City University of New york is employed as a guide. The result of this research shows a significant improvement in the rating of the essays after receiving feedback from ChatGPT. This is based on the Sig. value of paired sample test of .000, meaning a significant improvement is evident. Moreover, the interrater reliability between the raters is also high, as Cronbach’s Alpha shows a result of .912, indicating a value close to 1, meaning the rating process was reliable.